Journey around the sun : the story of Halley's comet - Gladstone, James, 1969- (Owlkids Books, 2021)
"Journey Around the Sun is the story of Halley's Comet, as told by the comet itself, as it returns to Earth approximately every 75 years. At the same time that we learn about the comet, we also learn about the history of human culture and technology, evolving as it has toward a greater understanding of our universe. Amazingly, although people in early civilizations did not know about the return orbit of Halley's Comet, documentation of the comet has survived from ancient China, Babylon, Greece, and the Arab world. (Comets were also painted in North and South America, but it's less clear whether or not they were of Halley.) These sightings were seen as omens good and bad, and they were woven into tapestries, painting on scrolls, immortalized in theatre. Edmond Halley predicted the comet would return in 1758, and he was proven right through successive technologies: telescopes, cameras, and eventually a spacecraft, Giotto, which photographed the comet's ice core at close range. Whether viewed through a cultural, psychological, or scientific lens, what's clear is that the history of Halley's comet is deeply tied to our own. The question that remains is what will Halley's Comet "see" the next time it comes to visit? The book ends with an Author's Note with more information about Halley's Comet and comets in general."--